Dopaminergic innervation at the central nucleus of the amygdala reveals distinct topographically segregated regions - Casey, Eric (2023)
The central nucleus of the amygdala (CeA) is involved in the expression of fear and anxiety disorders. Anatomically, it is divided into medial (CeM), lateral (CeL), and capsular (CeC) divisions. The CeA is densely innervated by dopaminergic projections that originate in the ventral periaqueductal gray/dorsal raphe (vPAG/DR) and the ventral tegmental area (VTA). However, whether dopamine (DA) exerts a homogenous control over the CeA or differentially regulates the various CeA subdivisions is still unknown. Here, we performed a neuroanatomical analysis of the mouse CeA and found that DAergic innervations from the PAG/DR and VTA constitute distinct, non-overlapping, pathways differing also in the relative expression of the dopamine transporter. By quantifying the distribution of DAergic fibers and the origin of DA inputs we identified two distinct regions in the CeL: a frontal region innervated by the VTA and vPAG/DR, a caudal region innervated only by the vPAG/DR, and three distinct regions in the CeC: fronto-dorsal innervated only by the VTA, fronto-ventral with sparse DAergic innervation, and a caudal region with low innervation from the vPAG/DR. In addition, we found that each region displays a distinct pattern of c-Fos activation following the administration of various DAeric drugs such as cocaine, SKF 38,393, quinpirole or haloperidol. In summary, we revealed unique properties of the DAergic pathways innervating the CeA, distinguishing six topographically segregated and functionally distinct regions. This unanticipated level of heterogeneity calls for more precise neuroanatomical specificity in future functional studies of the CeA.